The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1029/2004jd005271
|View full text |Cite
|
Sign up to set email alerts
|

Large nitric acid trihydrate particles and denitrification caused by mountain waves in the Arctic stratosphere

Abstract: [1] The contribution of stratospheric mountain waves to the formation of large nitric acid trihydrate (NAT) particles and subsequent denitrification of the Arctic polar vortex is calculated for the 1999/2000 winter using a three-dimensional (3-D) model. The model production mechanism involves the formation of NAT clouds with high particle number concentrations downwind of mountain wave ice clouds, as has been previously observed. These wave-induced NAT clouds then serve as ''mother clouds'' for the release of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…Further, our results are in agreement with Pitts et al (2011) who found an increase in ice PSC observations and coincident decrease in NAT mixture observations and suggested that this indicates heterogeneous nucleation of ice on NAT particles may be an important mechanism for the formation of synopticscale ice PSCs. In contrast, for the denitrification that was observed between 9-15 January sedimenting NAT particles that formed on mountain wave ice PSCs as has been discussed by Fueglistaler et al (2002), Dhaniyala et al (2002) and Mann et al (2005) could be a possible mechanism.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Further, our results are in agreement with Pitts et al (2011) who found an increase in ice PSC observations and coincident decrease in NAT mixture observations and suggested that this indicates heterogeneous nucleation of ice on NAT particles may be an important mechanism for the formation of synopticscale ice PSCs. In contrast, for the denitrification that was observed between 9-15 January sedimenting NAT particles that formed on mountain wave ice PSCs as has been discussed by Fueglistaler et al (2002), Dhaniyala et al (2002) and Mann et al (2005) could be a possible mechanism.…”
Section: Discussionmentioning
confidence: 61%
“…In contrast, for the denitrification that was observed between 9-15 January sedimenting NAT particles that formed on mountain wave ice PSCs as has been discussed by Fueglistaler et al (2002), Dhaniyala et al (2002) and Mann et al (2005) could be a possible mechanism.…”
Section: Psc Formation and Denitrificationmentioning
confidence: 61%
See 1 more Smart Citation
“…As a result, our understanding of gravity waves on a global-scale is considerably poorer than of the larger-scale stratospheric dynamics (Fritts and Alexander, 2003). Since gravity wave dynamics drive important aspects of the global stratospheric circulation, climate and chemical state (e.g., Alexander and Rosenlof, 2003;Mann et al, 2005), this lack of data represents an important gap in our knowledge.…”
Section: Introductionmentioning
confidence: 83%
“…However, modelling studies by Dhaniyala et al (2002) and Fueglistaler et al (2002) have shown that the dense NAT clouds produced downwind of mountain wave ice PSCs may subsequently act as sources for large NAT particles at low number concentrations throughout cold regions of the vortex by gradual sedimentation into the underlying NATsupersaturated air. Mann et al (2005) have explored the vortex-wide influence of such a mechanism and suggest that it may play a significant role in large NAT particle production and denitrification in the Arctic. However, methods of including such processes in largescale models have not yet been developed.…”
Section: Introductionmentioning
confidence: 99%